Rock magnetism of ejected basaltic boulders from Lonar crater, India: Implications for the existence of a short-lived impact-generated weak magnetic field - Arif, M.; Misra, Saumitra (My University, 2021)
The continuous ejecta deposit around the rim of Lonar impact crater, central India, contains angular basaltic boulders of size ≤5 m. These boulders experienced varying level of shock between 2–30 GPa due to impact, as indicated by the extreme fracturing of these basaltic boulders, fragmentation of plagioclase and titanomagnetite constituents of these ejected boulders, and the presence of maskelynite in them. We measure some rock magnetic properties, e.g., NRM/v (natural remanent magnetization [NRM]/bulk magnetic susceptibility [v]), REM (=NRM/saturation isothermal remanent magnetization [SIRM] ratio expressed in %), and anisotropy of magnetic susceptibility (AMS) on 53 subsamples from 18 oriented drill cores of the shocked ejected basaltic boulders from the eastern half of ejecta deposit in the present study. The measured data are similar in many respects to our previous observations on Lonar crater rim shocked basalts (Arif et al. 2012b). For example, a small population of the ejected basaltic boulder samples show very high NRM/v (between 378 and 989 Am_1; n = 7) and REM (between 1.5 and 7%; n = 4) and the AMS axes of these ejected basaltic boulders show triaxial distributions in stereographic projections. Moreover, some of the ejected basaltic boulders show higher values of squareness ratio (Mrs/Ms) and median destructive field (MDF) suggesting permanent changes in the intrinsic magnetic properties due to impact shock pressure. In stereographic plot, the high coercivity and high temperature (HC_HT) magnetization component of these ejected basaltic boulders are distributed in discrete clusters on the periphery of a small enveloping circle whose center (D = 108.0°, I = +69.2°) lies close to the HC_HT cluster of the crater rim shocked basalts. The center of this enveloping circle and the average HC_HT component of Lonar crater rim shocked basalts have the same statistical orientation, although the former has steeper dip. This distribution suggests the possibility that the ejected basaltic boulders, which were deposited during the modification stage of Lonar crater evolution, were magnetized in an impact-induced magnetic field that was rapidly decaying just after the impact. Our present study suggests that the ejected basaltic boulders and Lonar crater rim shocked basalts experienced high shock pressure (≥2 GPa) magnetization during impact.
Keywords: Rock Magnetism; Lonar Crater